The Lectorate of the Czech Language in Beijing in 1945-1960 - Roubal, Ales (Historica Olomucensia, 2014)
Czech studies as a study programme at the Beijing Foreign Studies University will celebrate the 60th anniversary. In 1952 Czechoslovakia and the People's Republic of China signed an agreement about the cultural cooperation, which significantly supported Czech studies in China. The beginning of Czech classes took place in the Chinese capital city Beijing at the Faculty of the Russian language, the Beijing Foreign Studies University in 1954 according to the decision of the Chinese Ministry of Education. The first lecturer of the Czech language was the sinologist Dana Stovickova. The lectorate successively employed two lecturers but at the end of 1950s, the international political situation got worse and for good reasons, Czechoslovakia was afraid of the future of the lectorate. Despite the insufficient financial and administrative background, teachers in cooperation with students published the first Czech-Chinese dictionary. During the first decade of the intensive cultural change between both states, a wide range of Chinese lecturers in Czech studies graduated, for instance Zhou Zhiyao, Zhu Weihua or He Lei. This paper brings information about the initial phase of the lectorate of the Czech language in Beijing.
Keywords: Lectorate; Czech language; lecturer in Czech studies; Beijing; teaching; student